(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يدرس هذا البحث موضوع "التشكيل الفني للقصيدة عند أدونيس" من خلال رصد مظاهر التجديد في اللغة الشعرية, الصورة الشعرية البنية الإيقاعية للقصيدة, وانتهاءً بالشكل المعماري للقصيدة ويتم ذلك من خلال عرض نظري لآراء مجموعة من الباحثين والنقاد في هذه القضايا, واختيار نماذج تطبيقية من إبداع أدونيس الشعري كشواهد على هذا التجديد والتطور. This research aims at studying the poem’s artistic format in Adonis’ work through tracing the innovation aspects as projected in the poetic language, poetic image, rhythmic structure of the poem and, finally, the architectural form of the poem. This will be done through a theoretical survey of the viewpoints of some researchers and critics, and selecting practical samples of Adonis’ poetic creativity to prove this innovation and development.